2019
DOI: 10.1038/s41467-019-12377-1
|View full text |Cite
|
Sign up to set email alerts
|

Tankyrase disrupts metabolic homeostasis and promotes tumorigenesis by inhibiting LKB1-AMPK signalling

Abstract: The LKB1/AMPK pathway plays a major role in cellular homeostasis and tumor suppression. Down-regulation of LKB1/AMPK occurs in several human cancers and has been implicated in metabolic diseases. However, the precise upstream regulation of LKB1-AMPK pathway is largely unknown. Here, we report that AMPK activation by LKB1 is regulated by tankyrases. Tankyrases interact with and ribosylate LKB1, promoting its K63-linked ubiquitination by an E3 ligase RNF146, which blocks LKB1/STRAD/MO25 complex formation and LKB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
56
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 48 publications
5
56
2
Order By: Relevance
“…LKB1 represents the primary AMPK upstream kinase and its phosphorylation at Ser428 is essential for LKB1‐induced AMPK activation (Gowans et al., 2013; Li et al., 2019). CaMKKβ is activated in response to an increase in intracellular Ca 2+ (Day et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…LKB1 represents the primary AMPK upstream kinase and its phosphorylation at Ser428 is essential for LKB1‐induced AMPK activation (Gowans et al., 2013; Li et al., 2019). CaMKKβ is activated in response to an increase in intracellular Ca 2+ (Day et al., 2017).…”
Section: Resultsmentioning
confidence: 99%
“…TNKS1/2 catalytic activity does not only regulate the stability of AXIN proteins, but also interferes with additional biological mechanisms and cell signaling pathways including telomere homeostasis, mitotic spindle formation, vesicle transport, and energy metabolism, as well as AKT/PI3K, AMPK and Hippo signaling 19,[24][25][26] . In Hippo signaling, tankyrase inhibitormediated stabilization of angiomotin (AMOT) proteins shifts the subcellular location of the transcription cofactors yes associated protein 1 (YAP) and tafazzin (TAZ), leading to a reduction of oncogenic YAP signaling 27,28 .…”
mentioning
confidence: 99%
“…Similar to these observations, both global deficiency and adipocyte-selective inactivation of TNKS1 lead to reduced fat mass [17,18]. A recent publication by Li et al showed improved glycemic control after administering 30 mg G007-LK/kg/day for 30 days, five times a week [43]. In contrast, in our study the inhibitor treatment (14 mg G007-LK/kg/day) did not reduce blood glucose, suggesting that a high dose of G007-LK may be required for achieving better glycemic control in db/db mice.…”
Section: Discussionmentioning
confidence: 59%
“…On the other hand, it has been shown in vitro in L6 myocytes, that TNKS inhibition results in reduced insulin stimulated glucose uptake [44]. If TNKS inhibition would increase insulin resistance in a similar manner in vivo, this could counteract the positive effect of weight loss on insulin sensitivity, though this contradicts with the study by Li et al [43]. The effects of TNKS inhibition on glucose uptake appear to be cell-type specific, as TNKS inhibition has been shown to enhance glucose uptake into adipocytes [45].…”
Section: Discussionmentioning
confidence: 82%